Bagaimana Tukar Tambah Handphode Pada Situs Jual Beli Online di Facebook - Amanda Awalia; Widya Febryari Anita (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to review how mobile trading is done on the online buying and selling site Facebook, and whether mobile trading is recommended on the online buying and selling site Facebook. This study uses a descriptive analysis method, which is a method for examining a group of people, an object, a condition, a system of thought or a class of events in the present. The data collection was carried out through written interview methods and tracing data on certain websites. The results obtained The trade-in practice is a legitimate community activity carried out to upgrade old cellphones to new cellphones. In addition to providing convenience and benefits for sellers, they have the opportunity to get more profits and can expand the market network because the opportunities to get new prospective customers will increase, and buyers have an advantage because the market price is below the counter price and they don't have to bother selling their old cell phones when they want to replace them with the new one. In addition, it provides benefits for Facebook because the increasing number of active users uses Facebook for economic and socio-cultural aspects. Recommendations for buyers who are already familiar with mobile technology.